Establishment and applications of quality management system for service industries - Yang, King-Jang; Chen, Shun-Hsing; Yang, Ching-Chow (International Journal of Financial, Accounting, and Management, 2020)
Purpose: Because of the limited resources and lack of knowledge and experience related to quality management, the service firms perform very few quality practices only, and result in a very limited effectiveness. In this research try to develop a systematic framework of quality management with several hierarchical constructs for service industries. Research methodology: This study also used Delphi and AHP method to examine the importance and the priorities of the five quality management stages and their involving practice activities, which are the valuable guideline for the service industries to successfully implement the quality management. Results: It is found that the service enterprises need to first assure the quality in service encounter, then can upgrade the implementation levels to delivery process and management system. But the practices in ‘total quality’ stage are the fundamental forces of the implementation of quality practices in the initial stages. Limitations: The AHP experts only comment on this issue not applicable to all industries. The research findings apply only to the service industry. Contribution: The service enterprises need to perform TQM successfully. After all the previous stages of quality management are performed very well, the service enterprises can raise the implementation level to the business quality. Keywords: Service industries, Service quality, Hierarchical quality management system, AHP method